Implementation Strategy of Motivation, Innovation, and Work Ethic on the Economic Performance of Papuan Nutmeg Farmers (Myristica Argantea) in Fakfak Regency - Fadlun Santi Rumain; Titis Istiqomah; Christina Wulansari; Vidia Gati (Research Trend in Technology and Management, 2023)
+ The economic performance of nutmeg farmers in Fakfak district is currently entering a period of very difficult challenges due to the age of nutmeg trees that are old, unmaintained, and no longer productive in bearing fruit. This empirical fact in the next few years will be a serious threat that can impoverish people due to low nutmeg yields; requires strategies that must be carried out by farmers to improve crop productivity. The research was carried out during May – December 2023. Descriptive research method with a combination of quantitative and qualitative analysis approaches. Data was obtained through a direct survey of respondents who had been deliberately determined. The data obtained are given a weight value based on the assessment indicators obtained from the results of the preliminary research. The validity and reliability of the data were tested gradually and in a structured manner using the triangulation and role sharing approaches. The results of the study are presented in the form of a spider web diagram equipped with illustrations of shift share gap values, Ishikawa diagrams, Pearson correlation analysis, and regression equation models obtained from the SPSS statistical device version 2.3.